IMPLEMENTASI SISTEM ANTRIAN ONLINE PADA DUKCAPIL KLATEN MENGGUNAKAN METODE USER CENTERED DESIGN (UCD) - Raharjo, Agus Budi; Aji, Adam Sekti (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2024)
The Population and Civil Registration Office (Dukcapil) has an important role in providing public services related to the processing of population documents. In Klaten Regency, people often face problems in taking care of legal identity documents at the Dukcapil, such as long and disorganized queues. The queuing system that is still done manually is considered less efficient and prone to fraud. The community also has difficulty in monitoring the order of the queue, so they have to wait a long time without certainty when they will be served. To overcome these problems, an integrated and computerized online queue information system is needed. This research aims to design and build an online queue information system at the Klaten Regency Dukcapil using the User Centered Design method. This system can provide better, efficient, and transparent services to the community. System development uses the Kotlin programming language and MySQL database. Black box testing is also carried out to find out the errors that exist in the system. Through the online queuing system, people can take queue numbers online and monitor the queue sequence in real time, thus providing convenience and comfort in accessing Dukcapil services. Thus, the quality of public services, especially in the processing of population documents, can be improved.